Pengaruh Teori Positivisme Hukum Terhadap Sistem Peradilan Pidana di Indonesia - Wahid Budiyono (Universitas Palangka Raya, 2024)
This study examines the influence of legal positivism theory on the criminal justice system in Indonesia. Legal positivism, which emphasizes the supremacy of written law, has significantly impacted the Indonesian criminal justice system. The study aims to investigate the extent to which legal positivism has shaped the principles, procedures, and practices within the criminal justice system in Indonesia The research method employed is a qualitative approach, utilizing doctrinal and empirical legal research methods. Data were collected through literature reviews, document analysis, and in-depth interviews with relevant stakeholders in the criminal justice system.The findings reveal that legal positivism has led to a rigid and formalistic approach within the Indonesian criminal justice system. This has resulted in a strong emphasis on the strict application of codified laws, often at the expense of considerations of justice, fairness, and societal needs. The study also identifies challenges and limitations in the current system, such as the over-reliance on written statutes, the limited role of judicial discretion, and the potential for disregarding the underlying principles of criminal lawThe implications of this study suggest the need for a more balanced and nuanced approach within the Indonesian criminal justice system, one that integrates the tenets of legal positivism with a greater emphasis on the principles of justice, proportionality, and the protection of individual rights. This study contributes to the ongoing discourse on the role of legal theory in shaping the criminal justice landscape in Indonesia.